(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The essay examines the most problematic profiles of the ruling of the Court of Santa Maria Capua Vetere. The Court ordered the implantation of embryos in utero even without the consent of the woman’s husband. In this regard there are many interesting profiles not only on the merit, but also in a procedural perspective.